Selective Iodination of Some Phenols, Anilines and Methoxyarenes by Molecular Iodine in the Presence of 1-Butyl-3-methylimidazolium Hydrogen Sulphate - Tajik, Hassan; Parsa, Fatemeh (Asian Journal of Chemistry, 2010)
A simple, mild and regioselective method for the iodination of some phenols, anilines and methoxyarenes by using molecular iodine in presence of 1-butyl-3-methylimidazolium hydrogen sulphate ([bmim]-HSO4) in acetonitrile as solvent is reported. One-pot synthesis, mild reaction conditions, short reaction times and excellent yields of the products are noteworthy.